A Comparison of Nursing Core Competency Frameworks in ASEAN Countries: A Document Analysis - Mohamad As’ad Efendy; Michael I. Aggari (Journal of Nursing Practice)
Background: The nursing profession in Southeast Asia is facing growing complexity due to demographic shifts, changing disease patterns, and rising demands for high-quality care. Regional efforts to enhance workforce mobility and standardize qualifications have led to the development of core competencies in common nursing. However, the national implementation remains inconsistent.